Effect of Tiliacora triandra leaf juice on qualities of Thai layered dessert - Chumkaew, Krittin; Punfujinda, Chaiyasit (Science, Engineering and Health Studies, 2019)
The physical and nutritional values of Thai layered dessert added with Tiliacora triandra (Colebr.) Diels (or yanang) leaf juice were studied. The results indicated the most appropriate proportion of yanang leaf juice for making Thai layered dessert was 5% since this proportion received the highest levels of acceptance. The physical characteristics analysis revealed that the hardness and springiness values of Thai layered dessert with more yanang leaf juice added were significantly lower (p≤0.05). The L* and b* color values were also significantly lower when more yanang leaf juice was added. Conversely, the a* value of the desserts increased when more yanang leaf juice was added. A comparison between the nutritional values found in Thai layered dessert with the yanang leaf juice and those found in such Thai layered dessert with pandan leaf juice added revealed that these two desserts contained different amounts of carbohydrate and calcium (p≤0.05). The Thai layered dessert with added yanang leaf juice contained 2.85 mg of calcium /100 g, which was higher than the amount of calcium found in the Thai layered dessert with added pandan leaf juice (p≤0.05).